An analysis of UK swap yields - Tanweer Akram; Khawaja Mamun (Levy Economics Institute of Bard College, 2022)
John Maynard Keynes argued that the central bank influences the long-term interest rate through the effect of its policy rate on the short-term interest rate. However, Keynes's claim was confined to the behavior of the long-term government bond yield. This paper investigates whether Keynes's claim holds for the yields of spread products and over-the-counter financial derivatives by econometrically modeling the dynamics of the pound sterling-denominated longterm interest rate swap yield. It uses the generalized autoregressive conditional heteroskedasticity (GARCH) modeling approach to examine the relationship between the month-over-month changes in the short-term swap yield and the month-over-month change in the long-term swap yield, while controlling for several key macroeconomic and financial variables. The month-overmonth change in the short-term interest rate has a positive and statistically significant effect on the month-over-month change in the long-term swap yield. This finding reinforces Keynes's conjecture concerning the central bank's influence over the long-term interest rate. The investigation's empirical findings and their policy implications are discussed from a Keynesian perspective.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Swaps; Swap Yields; Interest Rates; Bank of England; John Maynard Keynes